Is the ethics of right-mindedness the ethics of the self-realising man? - Skorupka, Alfred (Folia Philosophica, 2003)
The present article shows us the concept of the self-realising man as understood by A.H. Maslow, the main representative of the current called humanist psychology. The author states that the ethics of right-mindedness, devised by J. Banka, is the ethics of a self-realising human being. Thus, anyone who follows the principles of this kind of ethics makes the most of his or her possibilities. Such a person should be contrasted with a neurotic, who, in J. Banka’s terminology, is called a “mock-man” (lieczlowiek), who does not satisfy his human needs, does not develop, does not give expression to his or her personality, and prefers to put on “a mask”. It is the author’s intention to emphasise, in the present work, the mutual relations and similarities, existing without doubt between philosophical and psychological concepts.